2003
DOI: 10.1021/je0340710
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Study of Lysozyme in Dimethyl Sulfoxide + Water Solution at 298.15 K

Abstract: The densities, d, and fluorescence spectra of ternary mixtures of water (1) + dimethyl sulfoxide (2) + lysozyme (3) were measured, and the partial specific volumes of lysozyme, v̄°, were determined as the extrapolated values of the apparent partial specific volumes at an infinitely dilute concentration of lysozyme at 298.15 K. A binary mixture of water + dimethyl sulfoxide has a minimum excess volume when the mole fraction of dimethyl sulfoxide (x 2) is in the range 0.25 to 0.42, and lysozyme unfolds and aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…Figure 3 shows the dependence of the intrinsic viscosity on x 2 (A) together with our previous results of fluorescence spectra and partial specific volumes of lysozyme (B). 4 Our previous results show that there are at least three states in the denaturation process of lysozyme in DMSO: the native state (in water), the intermediate state (x 2 ) 0.05-0.2), and the denatured-aggregated state (x 2 > 0.4). It is clear that the intrinsic viscosity changed in these three states as was indicated by the results of fluorescence measurement in the denaturation process.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Figure 3 shows the dependence of the intrinsic viscosity on x 2 (A) together with our previous results of fluorescence spectra and partial specific volumes of lysozyme (B). 4 Our previous results show that there are at least three states in the denaturation process of lysozyme in DMSO: the native state (in water), the intermediate state (x 2 ) 0.05-0.2), and the denatured-aggregated state (x 2 > 0.4). It is clear that the intrinsic viscosity changed in these three states as was indicated by the results of fluorescence measurement in the denaturation process.…”
Section: Resultsmentioning
confidence: 91%
“…All solvents and solutions were prepared according to previously mentioned procedures. 4 Precise x 2 values for the solvents (water + DMSO) and solutions (water + DMSO + lysozyme) were respectively calculated using the weight of DMSO and water. The differences in x 2 between the solvents and the solutions were accurate to within 10 -4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a partial specific volume gives information about the protein-solvent interaction and about the changes in protein conformation. Studies of the partial specific volume of HEWL in water-DMSO solution (Kamiyama et al, 2003), water-ethanol solution (Sirotkin & Winter, 2010) and water-guanidinium chloride solution (Sasahara et al, 1999;Sirotkin & Winter, 2010) were reported before.…”
Section: Introductionmentioning
confidence: 99%
“…The volumetric thermodynamic properties (volume and its derivatives with respect to temperature, expansibility, and with respect to pressure, compressibility) have been widely employed in the study of folding/unfolding transitions due to changes in temperature [4][5][6][7], pressure [6,8], pH [7,[9][10][11][12][13], cosolvent composition [14,15], oxidation/ reduction reactions [16] and binding of ligand [17][18][19][20][21][22][23] because these properties are sensitive to the solute-solvent interaction (hydration) and to the intrinsic packing. In this respect, it has been suggested that the "efficacy of the use of volumetric measurements for solving problems of biological relevance ultimately depends on our ability to rationalize measured volumetric observables in terms of various volumetric inter-and intramolecular interactions including, but not limited to, hydration and intrinsic packing" [24].…”
Section: Introductionmentioning
confidence: 99%